Implementasi Program Digitalisasi UMKM melalui Pendampingan Aplikasi Keuangan Usaha Kelurahan Nyapah Kota Serang (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital-based public services and marketing systems. However, MSME actors in Nyapah Village, Walantaka District, Serang City, face limited digital literacy and have not optimally utilized digital platforms. This community service program aimed to improve the digital skills of MSME actors through socialization, training, and assistance in using the Business Finance application. The activity was conducted through collaboration between Universitas Bina Bangsa, Universitas Primagraha, and the Nyapah Village Government, beginning with the signing of an Implementation Agreement (IA) as a commitment to program sustainability. The methods included socialization, demonstrations, hands-on practice, assistance for three weeks, and evaluation of participants’ abilities. The results showed that participants were able to understand the procedures for using the Business Finance application, register accounts, access digital administrative services, and begin utilizing digital media as a means of business promotion. Continuous assistance positively impacted the improvement of the local community’s digital literacy and strengthened synergy between higher education institutions and the village government in supporting MSME digital transformation.